Fraud teori, dan keterkaitan dengan bidang akuntansi, manajemen, ethical culture, audit dan tehnologi: Suatu studi literatur - Sri Ambarwati; Susilawati Susilawati; Ameilia Damayanti; Roy Prakoso (AKURASI: Jurnal Riset Akuntansi dan Keuangan, 2023)
This article delves into various theories about fraud and their development, explaining why the theory of fraud is both broad and constantly evolving. The method used in this research was a literature study, referencing the period since the beginning of the development of the Fraud theory. Each theory is criticized for giving way to new variables, making the most appropriate contribution to scientific development, and explaining fraud prevention practices in companies. Research on fraud has been widely carried out both abroad and in Indonesia. The findings from this literature study reveal that fraud is inseparable from ethics. It is necessary to incorporate ethical elements into higher education curricula and to include aspects of information technology in theoretical models due to the increasingly advanced technological developments. It is necessary to incorporate ethical elements into higher education curricula and to include aspects of information technology in theoretical models due to the increasingly advanced technological developments. Public interest statement Fraud is not solely related to management accounting but also involves behavioral accounting and psychological aspects, which should be integrated because fraud involves organizational and human behavior.